2019
DOI: 10.1016/j.ntt.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of first trimester co-use of tobacco and Cannabis with prenatal immune response and psychosocial well-being

Abstract: Purpose.-This study aims to describe the association of first trimester co-use of tobacco and cannabis with maternal immune response and psychosocial well-being, relative to tobacco use only. Methods.-A preliminary midpoint analysis included 138 pregnant women with biologically verified tobacco use, 38 of whom (28%) also tested positive for recent cannabis use. Maternal perceived stress (Perceived Stress Scale), depressive symptoms (Edinburgh Postnatal Depression Scale), and serum immune markers (IL-1β, IL-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Further, a prospective examination of the relationship between symptoms of PTSD and cannabis use in pregnant women using ecological momentary assessments found that peak PTSD symptoms were significantly and temporally related to cannabis use (Sanjuan et al, 2019). In contrast, however, a cross-sectional examination of perceived stress scores with self-reported cannabis use during the first trimester indicated a null relationship (Ashford et al, 2019), perhaps due to overall low perceived stress scores, lack of variability, or reliance on self-reported use. Similarly, Ellis and colleagues (Ellis et al, 2019) did not observe a link between psychological distress and cannabis use during pregnancy among justice-involved women.…”
Section: Stress and Cannabis Use During Pregnancymentioning
confidence: 96%
See 2 more Smart Citations
“…Further, a prospective examination of the relationship between symptoms of PTSD and cannabis use in pregnant women using ecological momentary assessments found that peak PTSD symptoms were significantly and temporally related to cannabis use (Sanjuan et al, 2019). In contrast, however, a cross-sectional examination of perceived stress scores with self-reported cannabis use during the first trimester indicated a null relationship (Ashford et al, 2019), perhaps due to overall low perceived stress scores, lack of variability, or reliance on self-reported use. Similarly, Ellis and colleagues (Ellis et al, 2019) did not observe a link between psychological distress and cannabis use during pregnancy among justice-involved women.…”
Section: Stress and Cannabis Use During Pregnancymentioning
confidence: 96%
“…Similarly, Ellis and colleagues (Ellis et al, 2019) did not observe a link between psychological distress and cannabis use during pregnancy among justice-involved women. Together, these three studies (Ashford et al, 2019;Ellis et al, 2019;Sanjuan et al, 2019) suggest that the relationship between subjective stress and cannabis use may be complicated with daily fluctuation that may not be detectable via onetime assessments. Numerous demographic variables (e.g., younger age, lower education, lower income), use of other substances (e.g., nicotine, alcohol) during pregnancy, and depression are known predictors of cannabis use during pregnancy.…”
Section: Stress and Cannabis Use During Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…Low fatty acid amide hydrolase and high anandamide levels were initially associated with lower rates of embryo implantation, impaired decidualization, and higher risks of spontaneous miscarriage 56,68 . Recently, Ashford et al 69 examined the effects of cannabis and tobacco coexposure on the immune response of 138 women in the United States, during their first trimester of pregnancy. They observed decreased proinflammatory immune responses, as reflected by decreased tumor necrosis factor-a (TNF-a) levels, which may affect fetal outcomes.…”
Section: Adverse Obstetrical Outcomesmentioning
confidence: 99%
“…No significant differences (P , 0.05) were observed in the levels of other inflammatory markers [interleukin-1b (IL-1b), IL-2, IL-6, IL-8, and IL-10, C-reactive proteins, and matrix metalloproteinase-8 (MMP-8)]. In the absence of a cannabis-only group, it was impossible to conclude if the observed inflammatory effects resulted from cannabis only or a synergistic action with tobacco 69 .…”
Section: Adverse Obstetrical Outcomesmentioning
confidence: 99%